Total and harvest-date yield of processing tomato cultivars - Santos, G. M. [UNESP]; Cintra, A. A D [UNESP]; Braz, L. T. [UNESP]; Grilli, G. V G [UNESP]; Braz, B. A. (My University, 2004)
The productivity of 28 tomato cultivars was evaluated over three stages of harvest. The study was carried out during from June to December of 1999 in an open field at the experimental area of the Section of Olericulture and Aromatic Medicinal Plants, Department of Crop Production at FCAV-UNESP, Jaboticabal, SP, Brazil. The cultivars studied were H 7155, Hypeel, Andino, U 573, H 9036, IPA 6, H 9494, AG 33, Yuba, RPT 1294, AG 72, Pelmeech, Curico, Hypeel 45, RPT 1478, H 9492, H 9498, H 2710, Hitech 45, Halley, Botu 13, H 9553, U 646, NK 1570, AG 45, RPT 1095, RPT 1570, and PSX 37511. The experimental design was a randomized block design with four repetitions, with five plants per plot. Productivity was evaluated at three stages of harvest at 119, 149 and 179 days after seeding. There were no significant differences among the cultivars at the first harvest (119 days). The majority of the cultivars produced their highest yield at the second harvest; the most productive cultivars were Curicó and AG 72, which yielded 4.69 and 4.67 kg/plant, respectively, although they did not differ statistically from the cultivars Hypeel 45 (4.35 kg/plant) and H 9498 (4.16 kg/plant). Yields of the cultivars Andino and H 9494 were evenly distributed between the second and third harvests. At the third harvest, cultivar IPA 6 had the highest yield (2.9 kg/plant) and was statistically different from all other cultivars except H 9036 (2.34 kg). These two cultivars had the most delayed and concentrated maturity, making them suitable for mechanical harvesting, although at a later time. Cultivar AG 72 had the greatest total yield (5.76 kg/plant), but it was not statistically different from cultivars Hypeel 45 (5.43 kg), Curico (4.17 kg), H 9498 (4.83 kg), H 7155 (4.58 kg) and Halley (4.55 kg). All of the cultivars, with the exception of cultivars H 9036, IPA 6, Andino and H 9494 showed in the second harvest concentrated maturity, making it suitable for mechanical harvesting.
Keywords: Fruit quality; Lycopersicon esculentum Mill.; Yield